Investigating pulmonary and systemic pharmacokinetics of inhaled olodaterol in healthy volunteers using a population pharmacokinetic approach. (17th February 2016) - Borghardt, Jens Markus; Weber, Benjamin; Staab, Alexander; Kunz, Christina; Formella, Stephan; Kloft, Charlotte
Abstract : Aims: Olodaterol, a novel β2‐adrenergic receptor agonist, is a long‐acting, once‐daily inhaled bronchodilator approved for the treatment of chronic obstructive pulmonary disease. The aim of the present study was to describe the plasma and urine pharmacokinetics of olodaterol after intravenous administration and oral inhalation in healthy volunteers by population pharmacokinetic modelling and thereby to infer its pulmonary fate. Methods: Plasma and urine data after intravenous administration (0.5–25 μg) and oral inhalation (2.5–70 μg via the Respimat® inhaler) were available from a total of 148 healthy volunteers (single and multiple dosing). A stepwise model building approach was applied, using population pharmacokinetic modelling. Systemic disposition parameters were fixed to estimates obtained from intravenous data when modelling data after inhalation. Results: A pharmacokinetic model, including three depot compartments with associated parallel first‐order absorption processes (pulmonary model) on top of a four‐compartment body model (systemic disposition model), was found to describe the data the best. The dose reaching the lung (pulmonary bioavailable fraction) was estimated to be 49.4% [95% confidence interval (CI) 46.1, 52.7%] of the dose released from the device. A large proportion of the pulmonary bioavailable fraction [70.1% (95% CI 66.8, 73.3%)] was absorbed with a half‐life of 21.8 h (95% CI 19.7, 24.4 h). Conclusions: The plasma and urine pharmacokinetics of olodaterol after intravenous administration and oral inhalation in healthy volunteers were adequately described. The key finding was that a high proportion of the pulmonary bioavailable fraction had an extended pulmonary residence time. This finding was not expected based on the physicochemical properties of olodaterol.